2012
DOI: 10.5194/amt-5-759-2012
|View full text |Cite
|
Sign up to set email alerts
|

Operational considerations to improve total ozone measurements with a Microtops II ozone monitor

Abstract: Abstract.A Microtops II "ozone monitor" with UV channels centered at 305.5, 312.5, and 320 nm has been used routinely in six experimental campaigns carried out in several geographic locations and seasons, covering latitudes from 35 to 68 • N during the last ten years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). The total ozone content is retrieved by Microtops II by using different combinations (Channel I, 305.5/312.5 nm; Channel II, 312.5/320 nm; and Channel III, 305.5/312.5/320 nm) of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…5: 1020.0±1.5 nm, with nominal FWHM of 10.0±1.5 nm) [Morys et al, 2001a[Morys et al, , 2001b. The UV channels are used to measure the ozone vertical content [Gómez-Amo et al, 2012]. The NIR Ch.…”
Section: The Microtops-ii Ozone Monitor Sun Photometermentioning
confidence: 99%
See 1 more Smart Citation
“…5: 1020.0±1.5 nm, with nominal FWHM of 10.0±1.5 nm) [Morys et al, 2001a[Morys et al, , 2001b. The UV channels are used to measure the ozone vertical content [Gómez-Amo et al, 2012]. The NIR Ch.…”
Section: The Microtops-ii Ozone Monitor Sun Photometermentioning
confidence: 99%
“…This error source can be quantified by knowing the uncertainties of MIIOM ozone retrievals O 3 . By comparing MIIOM with Brewer spectrophotometer ozone retrievals, errors of a few percent have been found [Gómez-Amo et al, 2012]. By considering a conservative value of ±10% for O 3 ∕[O 3 ] and an ozone optical depth of about 0.62, 0.28, and 0.10 at Ch.…”
Section: 1002/2017jd026723mentioning
confidence: 99%
“…plateau on the north-eastern coast of Lampedusa, at the Station for Climate Observations maintained by ENEA (the Italian National Agency for New Technologies, Energy and Sustainable Economic Development). At this site, continuous observations of greenhouse gases (Artuso et al, 2009(Artuso et al, , 2010, aerosol properties Meloni et al, 2006;Pace et al, 2006), total ozone (Gómez Amo et al, 2012), ultraviolet irradiance (di Sarra et al, 2002; Harrison et al, 1994). The MFRSR is a sevenchannel radiometer which measures global and diffuse irradiances, and allows for the determination of column aerosol optical depth at five wavelengths (416, 496, 615, 671, and 869 nm).…”
Section: Samplingmentioning
confidence: 99%
“…The MICROTOPS II ozonometer replaces this instrument due to its suitability, i.e. small size, easily operated and less expensive (Gómez‐Amo et al ., ). Holdren et al .…”
Section: Introductionmentioning
confidence: 99%
“…The MICROTOPS II ozonometer replaces this instrument due to its suitability, i.e. small size, easily operated and less expensive (Gómez-Amo et al, 2012). Holdren et al (2001) found a significant correlation between MICROTOPS II and Dobson spectrometer observations.…”
Section: Introductionmentioning
confidence: 99%